Internal determinant of commercial bank’s profitability in Malaysia - Fitri Maharani, Nurdin (2021)
Commercial banks play a crucial role in the country’s economic growth and financial stability. Commercial banks receive customer deposits and lend the money to people who need it for business or other commercial purposes. This study determines the financial performance of commercial banks in Malaysia. It will provide an overview and comprehensive knowledge of the financial performance of banks and identify factors that influence the performance of banks. Bank size, capital adequacy, deposits and bank loans are key factors of profitability (ROA). This study, however, focuses solely on commercial banks operating in Malaysia spanning 5 fiscal years between 2015 and 2019. 10 commercial banks, including CIMB Bank, Malayan Banking Berhad, RHB Bank, Hong Leong Bank and Public Bank, OCBC Bank, Malaysia, Berhad Citibank Berhad, HSBC Deutsche Bank and United Overseas Bank, were selected to represent commercial banks in Malaysia (M). For this purpose, empirical data from DataStream and the Annual Report were collected. Using regression analysis, the research findings revealed that capital adequacy and bank loan had a significant impact on the profitability of Malaysian commercial banks. The findings of this study are extremely important and beneficial for market participants, the growth of the Malaysian economy, and as well as all commercial banks. The growth of the banking sector highly depends on sound decision-making, which enhances bank productivity and performance.